Case Report: ST-Segment Elevation in a Man With Acute Pericarditis - Li, Yi-Ming (Front Cardiovasc Med, 2020)
Background: Acute pericarditis is a rapid inflammatory condition of the pericardium with both infectious and non-infectious etiology. Most acute pericarditis is self-limited, with a small portion evolving rapidly. The definitive diagnosis of acute pericarditis often requires detailed physical examination, ECG, echocardiography, blood analysis and chest X-ray. It's usually challenging to distinguish acute pericarditis from ST-elevated myocardial infarction (STEMI) due to the similar ECG characteristics (ST segment change). Here we present a case of purulent pericarditis probably caused by esophageal perforation. Case: A 52 year-old male presented with chest pain and dyspnea for 16 h. ST-segment elevation and positive cardiac markers lead to the initial diagnosis of ST-elevated myocardial infarction. Coronary angiography demonstrated normal coronary artery, while transthoracic echocardiography (TTE) showed massive pericardial effusion. Then, pericardiocentesis was performed with 250 ml of yellowish-green pus-like fluid extracted. A detailed history examination revealed a week history of possible esophageal perforation caused by a fishbone. And a further computed tomography (CT) demonstrated the presence of pneumomediastinum, and effusions in mediastinum, which lead to the diagnosis of purulent pericarditis. However, the patient's family refused further treatment and the patient died soon after discharge. Conclusion: The differential diagnosis of chest pain should include acute pericarditis, which can be equally critical and fatal. And it's important to note the peculiar characteristics of acute pericarditis, which include concave and diffused ST-segment elevation, PR segment depression, and the ratio of ST-segment elevation to T wave >0.24 in lead V6. Moreover, comprehensive medical history and physical examination are crucial to the differential diagnosis of chest pain patients.